PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL TERHADAP KECURANGAN AKUNTANSI (SURVEI PADA KARYAWAN PERUSAHAN ASURANSI DI KOTA BENGKULU) - Vanisha Patika Sari; Baihaqi Baihaqi (ITB AAS Indonesia Surakarta, 2024)
This research aims to examine the influence of intellectual intelligence, emotional intelligence and spi/ritual intelligence on accounting fraud. Through the use of a purposive sampling technique, this research has been conducted on 33 employees of insurance companies in with the insurance companies in the city of BengkuluA quantitative methodology will be employed in this study. The approach used by the research to collect the data includes the distribution of questionnaires to the accounting and financial staff of insurance companies in Bengkulu city to collect primary data. IBM SPSS Statistics 26 analyzed the collected data utilizing multiple linear regression. This research show that indicate that intellectual intelligence, emotional intelligence, and spiritual intelligence have a negative effect on accounting fraud.